The role of manual thrombectomy in cardiovascular outcome among patients with total cutoff vessel myocardial infarction undergoing primary percutaneous coronary intervention - Alireza Khosravi (ARYA Atherosclerosis, 2017)
BACKGROUND: The applicability of manual aspiration thrombectomy in patients with ST-segment elevation myocardial infarction (STEMI) has been a challenging issue. This study aimed to compare the impact of additive manual thrombectomy on patients with myocardial infarction (MI) and total cutoff vessel with standard primary percutaneous coronary intervention (PPCI) with bailout thrombectomy. METHODS: In this case-control study, 181 patients with acute STEMI were enrolled who referred to Chamran Hospital (Isfahan, Iran) between August to December 2014. The culprit lesion was treated with routine PPCI with bailout thrombectomy (111 patients) and routine primary thrombectomy then percutaneous coronary intervention [(PCI), 70 patients] during hospitalization and one month after discharge. Patients in the case group received manual thrombectomy before PPCI and patients in the control group received standard PPCI with bailout thrombectomy. Patients were followed during the study procedure, post-hospitalization and one month later for cardiovascular outcomes including death, recurrent MI, stroke, major bleeding, post PCI arrhythmia, no reflow, thrombolysis in myocardial infarction (TIMI)-flow and TIMI myocardial blush grade (TMBG), which were assessed and recorded. RESULTS: Myocardial perfusion and angiographic outcomes had no significant differences in the two groups (P = 0.730). There was also no significant difference in no reflow prevalence between the two groups (P > 0.990). There were no significant differences for primary outcomes such as death, stroke, major bleeding and arrhythmia between the two groups (P < 0.050). In particular, outcomes were the same for both groups during hospitalization period and one month after discharge. Mortality rate during hospitalization was 5.7% for the control group and 4.5% for the case group (P = 0.730). However, one-month mortality rate was quite similar in both groups. CONCLUSION: This study showed there is no significant difference in cardiovascular outcomes such as death, stroke, bleeding, arrhythmia, target vessel revascularization, and distal embolization during hospitalization and one month after discharge in patients with acute MI and total cutoff of the involved vessel, who underwent PPCI with and without primary Export® aspiration catheter direct thrombosuction.